2016
DOI: 10.5430/jnep.v6n11p104
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on transfer of learning by nursing students in primary healthcare facilities

Abstract: Supportive work environments promote professional socialisation and integration of theory in practice. Qualitative data generated through four nominal groups were deductively analysed using the components of the systemic model of training transfer. This article reports on the perspectives of nurse clinicians, clinical facilitators, and students from the training institution regarding aspects of student characteristics, educational design, transfer climate and work environment that influence nursing students' t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…This is especially true in nursing where students learn in class, from books, lectures, or simulations and then must transfer learning to the patient care setting. The impact of student characteristics, educational design, transfer climate, and work environment on learning transfer have been examined . Forbes found that critical thinking skills are transferrable when learning in a different discipline, but require explicit guidance from educators.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is especially true in nursing where students learn in class, from books, lectures, or simulations and then must transfer learning to the patient care setting. The impact of student characteristics, educational design, transfer climate, and work environment on learning transfer have been examined . Forbes found that critical thinking skills are transferrable when learning in a different discipline, but require explicit guidance from educators.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies related to transfer have been carried out nowadays, especially among newly graduated professionals or students [ 26 , 27 , 28 ]. However, the purpose of this study is to analyse whether, after receiving e-health or e-skills training, the professional applies it to their work, both for their own performance and for the benefit of patients.…”
Section: Introductionmentioning
confidence: 99%
“…16,23 One nursing program developed a competency-based education model to award college credit for prior military training and skill development. 20 Research validates that learning transfer is not merely the result of individual characteristics but rather depends on the educational design, learning and clinical environments, and collaboration between academic and workplace institutions [24][25][26] . López, Springer, and Nelson 27 suggested academic success for student veterans relies on teaching and learning practices to build on life experiences, promote classroom environment socialization, and accommodate diverse learning styles along with curricular coherence allowing for the transfer of prior knowledge.…”
mentioning
confidence: 99%